A Study of Seasonal Abundance of Aquatic Birds including Migratory Birds with a Special Attention on population of Bar-headed Geese at Magadi Kere, Shirahatti Taluk, Gadag District, Karnataka, India - Kshirsagar, Yashpal; Vrishni, Sonal; Ratan, Anil Kumar; Vibhuti, Shidramappa L (Indian Forester, 2022)
A study of seasonal abundance of aquatic birds including migratory birds with a special attention on population of Bar-headed Geese coming from Siberia and Tibet to Magadi Kere, Shirahatti Taluk, Gadag District Karnataka was conducted over a period of five years spanning from March 2015 to March 2020. A total of 34 aquatic bird species were observed and recorded. The abundance and frequency of visits of migratory birds especially of Barheaded Geese at different time intervals was recorded and inferences were drawn. The Bar-headed geese followed a fixed pattern of migration with the season starting from October-November, reaching the highest count in January-February and finally subsiding in March-April every year. It is also discerned from the study that the feeding pattern of aquatic birds coincides with the local crops grown in the vicinity, which are nearly at harvesting stage during the peak season of migration.